Between the greek tragedy and the road movies: Fernando Arrabal’s Iré como un caballo loco (1973) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article makes an analysis of the narrative structure, of the aesthetics and content of Fernando Arrabal’s film work Iré como un caballo loco (1973). Beyond his acknowledged trajectory as a playwright, this unique work constructs -in a deep and structured way- a complex narrative, full of biographical, literary and media referents, beyond the mere appearance of chaos, confusion and absurdity. The intertextuality of its narrative structure forces a qualitative and interdisciplinary analysis to reach the most hidden and unsuspected aspects of the film, where nothing is accidental. Among the main contributions are a narrative and structural duality that connects both with Aeschylus and also with journey and road movies.
Keywords: Fernando Arrabal; spanish cinema; Aeschylus; road movies